High-risk screening of late-onset Pompe disease: A different early portrait in China - Jiao, Kexin; Dong, Jihong; Luo, Sushan; Yu, Liqiang; Ke, Qing; Wang, Zhiqiang; Luan, Xinghua; Zhang, Xiaojie; Guo, Junhong; Chen, Yan; Li, Xihua; Tan, Song; et al. (Frontiers in Neurology, 2022)
Introduction: The lack of knowledge regarding the differences between Chinese and other ethnicities in the early manifestation of late-onset Pompe disease (LOPD) prohibits the development of an effective screening strategy. We conducted a multicenter screening study to determine LOPD prevalence in high-risk populations and define the early manifestation of LOPD in China. Methods: Between August 2020 and April 2021, the participants were prospectively identified through medical examination at 20 centers from inpatient departments and outpatient neuromuscular clinics in China. The inclusion criteria were as follows: (1) age ≥ 1 year and (2) either one of the following conditions: a) persistent hyperCKemia, b) muscle weakness of the axial and/or limb-girdle muscles, or c) unexplained restrictive respiratory insufficiency. Enzymatic activity of acid α-glucosidase (GAA) was measured in a dried blood spot (DBS) using tandem mass spectrometry (MS/MS) assay. Next-generation sequencing was used to evaluate all samples with decreased GAA activity, searching for GAA mutations and pseudodeficiency alleles. Results: Among the 492 cases, 26 positive samples (5.3%) were detected in the DBS test. Molecular studies confirmed a diagnosis of LOPD in eight cases (1.6%). Using MS/MS assay, GAA activities in individuals with pseudodeficiency could be distinguished from those in patients with LOPD. The median interval from the onset of symptoms to diagnosis was 5 years. All patients also showed respiratory insufficiency, with a mean forced vital capacity of 48%, in addition to axial/proximal muscle weakness. The creatine kinase level ranged from normal to no more than 5-fold the upper normal limit. LOPD with isolated hyperCKemia was not identified. Conclusion: Less frequent hyperCKemia and predominant respiratory insufficiency depict a different early portrait of adult Chinese patients with LOPD. A modified high-risk screening strategy should be proposed for the early diagnosis of Chinese patients with LOPD.